Revolutionizing Endoscopic Tools: An Innovative Approach to Driving Mechanism Design - Newaz, Abdullah Al Hossain; Jahan, Refat (Science and Technology: Developments and Applications Vol. 10, 2025)
The search for more accurate and less invasive techniques in surgery has led to the ongoing advancement of biomedical tools, with endoscopic instruments being particularly important in modern surgeries. These sophisticated tools grant surgeons the ability to conduct delicate operations with unparalleled precision and control. Endoscopic instruments have revolutionised the field of surgery by minimising the physical impact of surgical interventions, improving patient recovery times, and expanding the possibilities for both treatment and diagnosis. This study showcases a new driving mechanism designed specifically for endoscopic instruments, with the goal of overcoming current limitations in terms of control, reliability, and user friendliness. By combining advanced engineering concepts with the unique needs of surgical procedures, this innovative design represents a substantial improvement in the functionality and effectiveness of endoscopic equipment. This study introduces a mechanism that aims to improve the precision of surgical procedures and reduce patient trauma through rigorous design processes such as mechanical calculations and ergonomic considerations. Design and parts assembled using Creo 9.0 software. This chapter covers the entire design process from conceptualisation to detailed engineering analysis, highlighting the potential for future advancements in the field. It emphasises the importance of engineering innovation in expanding possibilities in biomedical instrumentation to enhance surgical outcomes and patient care. Finally, the study discusses prospects, including the integration of smart materials, advanced imaging technologies, and possibly robotic automation, which could further revolutionise surgical practices.